Comparative Analysis of OLSR and DSR Routing Protocol Performance on Vehicular Ad Hoc Network (VANET) - Safrianti, Ery; Sari, Linna Oktaviana; Romadan, Ahmad; Feranita, Feranita (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2023)
Communication between vehicles is essential in increasing comfort and safety for drivers and passengers. Technology advancements offer a new concept: the Vehicular Ad Hoc Network (VANET). The VANET network allows vehicles on the road to communicate directly with other vehicles while moving and without using the fixed infrastructure. A routing protocol is needed to facilitate communication in the network. Routing protocols are used to find routes between nodes to send messages to each other and forward packets along the selected route. In this study, a comparative analysis of the performance of the topology-based routing protocols will be carried out: Optimized Link State Routing (OLSR) and Dynamic Source Routing (DSR) on VANET with a case study of urban road scenarios. Both protocols are simulated using Network Simulator 2 (NS-2) with a scenario of changing the number of nodes. The two protocols were compared and analyzed from the parameters of packet delivery ratio, end-to-end delay, routing overhead, throughput, packet loss, and collision rate. Based on the simulation results, the overall DSR routing protocol has a better performance value with an average Packet delivery ratio of 99.92%, End-to-end delay of 0.0894 ms, Routing overhead of 1,000 ms, the throughput of 261.55 kbps, Packet loss of 0.0778% and collision rate 1.8770. While the OLSR routing protocol has an average value of Packet delivery ratio of 99.89%, End-to-end delay of 0.0878 ms, Routing overhead of 1,000 ms, throughput of 230.27 kbps, Packet loss of 0.1007%, and collision rate of 1.6687.